Métodos de incentivo à denúncia de ilícitos: subsídios para a implementação de programas whistle-blowing perante agências e órgãos reguladores brasileiros - Ferreira, Adriano Valente Torraca (2019)
The objective of this research is to investigate the possibility of creating Whistle-Blowing Programns in Brazil, with a focus on their application in the regulated sectors. Noting the results achieved by foreign federal agencies in similar contexts, we presented the dates of the irregularity reporting programs and presenting the main legislative initiatives that addressed the issue in Brazil. Then, we also evaluate the tools tools to encourage the use of denunciation models: (1) promulgation of protection to the rapporteurs, (2) promise of rewards and (3) imposition of reporting duties.